Evaluation of primitive ground water supplies as a risk factor for the development of major waterborne zoonosis in Egyptian children living in rural areas - Hassan A. Elfadaly; Nawal A. Hassanain; Mohey A. Hassanain; Ashraf M. Barakat; Raafat M. Shaapan (Elsevier, 2018)
Background: Endemic waterborne zoonosis frequently occurs in both developed and less developed countries. Thus, bio-surveillance of waterborne zoonosis is a "necessity" for the implementation of effective preventive public health measures in Egyptian rural areas. The primitive individual water supplies created by the rural agriculture population, primarily from ground water, usually maximize the customers' exposure to impurity pathogens via diffused humans and animal excreta or wastages. The current study aimed to evaluate the frequency of zoonotic pathogens within the infiltrated untreated ground water supplies with an assessment of the impact of such biohazards on children living in the studied Egyptian rural areas. Methods: A total of 796 stool samples were collected from children under 10 years of age from the Abulnomorous (401) and Shabramant (395) villages in Giza, Egypt, and two hundred forty five ground water samples were collected from various individual home water supplies (ground pumps) within two rural Egyptian localities, namely, the Abulnomorous (128) and Shabramant (117) villages. All the samples were examined for the identification of bacterial, fungal and parasitic zoonosis. Results: The isolation of Campylobacter jejuni, Escherichia coli, Salmonella typhi and Shigella spp. was documented in the following frequencies in the water and stool samples of symptomatic children (11.4% and 5.2%), (6.9% and 2.9%), (13.9% and 6.4%) and (4.5% and 2.3%), respectively. Candida albicans and Cryptococcus neoformans were detected in the examined water and morbid stool samples at (7.8% and 2.9%) and (1.6% and 0%), respectively. Additionally, the existence of parasites, including Entamoeba histolytica (5.7% and 4%), Giardia lamblia (9% and 1.7%) and Cryptosporidium oocysts (15.1% and 3.5%), was determined. Regarding Toxoplasma gondii, sporulated oocysts were detected in the ground water (2.9%). The prevalence of diarrhea among the examined children in Abulnomorous was higher (24.7%) than those living in Shabramant (18.7%), which might be attributable to the higher presentation of associated social and environmental risk factors in Abulnomorous than in Shabramant with significant differences P ≤ 0.05. Additionally, the ground water analysis showed that the water samples collected from Abulnomorous (83.0%) were more polluted than those from Shabramant (74.3%). Conclusions: The results confirm human biohazards through rural individual water supplies and reflect the need for public health education regarding the correct use of drinking ground water only after effective treatment through filtration and/or boiling. Keywords: Ground water borne zoonosis, Egyptian rural community, Morbid children, Gastroenteritis